Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah (PAD) Kota Cimahi Tahun 2010-2019 - Ria Aprilia Purbaya; Ahmad Syarief; Mia Rosmiati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study is to determine of the influence of several factors such as Gross Regional Domestic Product (GRDP), Population, and Investment either partially or simultaneously on Cimahi City Locally-Generated Revenue (PAD) 2010-2019. In this research use quantitative method with descriptive approach. The data used in this research are secondary data from statistical data and also financial statements of Cimahi City in 2010-2019. The data analysis method used is the classical assumption test and hypothesis testing with multiple linear regression analysis using SPSS Software. The results of the research partially show that just population has significant effect on Cimahi City’s Locally-Generated Revenue. The results of the research simultaneously show that GRDP, Population, and Investment have a positive and significant together effect on the Cimahi City’s Locally-Generated Revenue.